2022
DOI: 10.1038/s41598-022-11675-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fish meal substitution by clam meal on the growth and health of Florida pompano (Trachinotus carolinus)

Abstract: A 12-week feeding trial was conducted to evaluate the effects of fish meal (FM) substitution by clam meal (CM, at 10%, 20% and 30% of the diet) on the growth, feed utilization, hepatic antioxidant enzymes, plasma parameters, fatty acid and amino acid composition, and gut microbiome of juvenile Florida pompano, Trachinotus carolinus. The results indicated that: (1) juveniles fed 10% and 20% CM had a significantly higher final weight than the group fed the control (0% CM); and the control group also showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Furthermore, one method to evaluate the adequacy of EFA provided in a diet is to evaluate the ratio of specific EFA in fish tissues with respect to the EFA provided by the diet, i.e., the fish to diet (FD) ratio [80]. This FD ratio could help to understand which EFA might be conserved, deficient, or selectively retained in terms of EFA in fish juveniles [32,80]. In the present study, the FD ratios for the total omega-3 fatty acids and PUFA for all treatments were around 1 (≤1), suggesting that the requirements for EFAs were met when Atlantic salmon parr fed the mealworm diets as fishmeal does.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, one method to evaluate the adequacy of EFA provided in a diet is to evaluate the ratio of specific EFA in fish tissues with respect to the EFA provided by the diet, i.e., the fish to diet (FD) ratio [80]. This FD ratio could help to understand which EFA might be conserved, deficient, or selectively retained in terms of EFA in fish juveniles [32,80]. In the present study, the FD ratios for the total omega-3 fatty acids and PUFA for all treatments were around 1 (≤1), suggesting that the requirements for EFAs were met when Atlantic salmon parr fed the mealworm diets as fishmeal does.…”
Section: Discussionmentioning
confidence: 99%
“…-0. In fish nutrition studies, blood parameters including total protein, ALP, ALT, IgM, and TIBC are important indicators for health status in response to dietary manipulations of European sea bass [14], Indian major carps, Labeo rohita, Catla catla, and Cirrhinus mrigala [26], red seabream [27], blunt snout bream, Megalobrama amblycephala [35,45,81], largemouth bass, Micropterus salmoides [29,31,82], and Florida pompano, Trachinotus carolinus [32]. The total protein in plasma is related to the enhancement of digested protein [81,83,84].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Romboutsia can be isolated in the gut of a variety of animals both aquatic and terrestrial ( Gerritsen et al, 2019 ). It has been shown that Romboutsia are significantly enriched in fish fed fishmeal ( Habte-Tsion et al, 2022 ). Romboutsia was the only genus which showed a significant positive correlation with nitrogen and phosphorus in this study ( P < 0.05 ).…”
Section: Discussionmentioning
confidence: 99%